Relationship of the Islamic Religious Education Subjects and Covid-19 Pandemic Atmosphere to Students Religiosity - Moch. Rizal Fuadiy; Siti Novia Rohmah (LP2M Sekolah Tinggi Agama Islam Nahdlatul Ulama Pacitan, 2021)
This study aims to determine how much influence the subjects of Islamic-Religious-Education subjects during COVID-19 pandemic atmosphere on student’s Religiosity. This research uses quantitative research with associative methods. The data sources obtained are primary data. The data analysis process uses multiple regression analysis, with Islamic-Religious-Education Subjects ( ) and Covid-19 Pandemic atmosphere ( ) as independent variables then Religiosity as dependent variable (Y). The study shows that Islamic-religious-education subjects have a positive and significant influence on student’s religiosity. The Covid-19 pandemic atmosphere does not have a positive and significant effect on student’s religiosity.